Archiving Food Heritage Towards Championing Food Security: A Case Study of Lokalpedia - Raymundo Jr., Allan (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2024)
Key anthropologists have previously looked into the potential of using “geographical indications” to protect localities and their products, but little has been said about the role food heritage could play in championing food security. This paper looks into the open access archive of local and endemic food stuff, Lokalpedia, that is at the forefront of championing ingredients endemic to the Philippines and advocating for their preservation, and, in extension, the livelihood of farmers, fisherfolk, and market vendors. Through social media content analysis and literature review, this paper explores and builds the case for the potential of archiving and understanding local and traditional food ingredients and local produce toward a more holistic and meaningful approach to ameliorating food insecurity. By rendering these local food products visible in both the local and global arena, it attunes communities to foodstuff available in their localities and entices culture-savvy consumers to support local food producers.